Differential Activity of Voltage- and Ca2+-Dependent Potassium Channels in Leukemic T Cell Lines: Jurkat Cells Represent an Exceptional Case - Valle-Reyes, Salvador; Valencia-Cruz, Georgina; Liñan-Rico, Liliana; Pottosin, Igor; Dobrovinskaya, Oxana (Frontiers in Physiology, 2018)
Activation of resting T cells relies on sustained Ca2+ influx across the plasma membrane, which in turn depends on the functional expression of potassium channels, whose activity repolarizes the membrane potential. Depending on the T-cells subset, upon activation the expression of Ca2+- or voltage-activated K+ channels, KCa or Kv, is up-regulated. In this study, by means of patch-clamp technique in the whole cell mode, we have studied in detail the characteristics of Kv and KCa currents in resting and activated human T cells, the only well explored human T-leukemic cell line Jurkat, and two additional human leukemic T cell lines, CEM and MOLT-3. Voltage dependence of activation and inactivation of Kv1.3 current were shifted up to by 15 mV to more negative potentials upon a prolonged incubation in the whole cell mode and displayed little difference at a stable state in all cell lines but CEM, where the activation curve was biphasic, with a high and low potential components. In Jurkat, KCa currents were dominated by apamine-sensitive KCa2.2 channels, whereas only KCa3.1 current was detected in healthy T and leukemic CEM and MOLT-3 cells. Despite a high proliferation potential of Jurkat cells, Kv and KCa currents were unexpectedly small, more than 10-fold lesser as compared to activated healthy human T cells, CEM and MOLT-3, which displayed characteristic Kv1.3high:KCa3.1high phenotype. Our results suggest that Jurkat cells represent perhaps a singular case and call for more extensive studies on primary leukemic T cell lines as well as a verification of the therapeutic potential of specific KCa3.1 blockers to combat acute lymphoblastic T leukemias.